Current Strategies for Managing Providers Infected with Bloodborne Pathogens - Turkel, Sarah (Infect Control Hosp Epidemiol, 2011)
BACKGROUND: In 1991 CDC issued guidelines to reduce risks for provider-to-patient transmission of bloodborne pathogens. These guidelines, unchanged since 1991, recommend management strategies for hepatitis B ‘e’ antigen-positive providers and for providers infected with human immunodeficiency virus (HIV); they do not address hepatitis-C-virus (HCV)-infected providers. OBJECTIVE: We summarize current state practices and surveyed state health departments to determine: 1) if state policies have been modified since 1991; 2), if state laws require prospective notification of patients and/or expert review panels to manage infected providers; 3) the frequency with which infected-providers issues come to the attention of state health departments; and 4) how state health departments intervene. METHODS: We reviewed all 50 states’ laws and guidelines to determine current practices and conducted a structured telephone survey of all state health departments. RESULTS: Whereas only 19 states require infected providers to notify patients of the providers’ bloodborne pathogen infection, these 19 states require notification under highly varied circumstances. Only ten of 50 state health department officials identified these issues as requiring significant departmental effort. No state law or guideline incorporates information about providers’ viral burdens as part of the risk assessment. Only 3/50 States have modified policies or laws since initial passage; and only 1/50 discusses the management of HCV-infected providers.. CONCLUSIONS: These results identify a need for incorporating contemporary scientific information into guidelines and also suggest that infected-provider issues are not occurring commonly, are not being detected, or that they are being managed at levels below the state health department.